2004
DOI: 10.1016/j.febslet.2004.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Transferrin receptor 1 mRNA is downregulated in placenta of hepcidin transgenic embryos

Abstract: We have previously shown that hepcidin transgenic embryos are severely anemic and die around birth. Here, we report that embryonic hepcidin transgene expression decreases transferrin receptor 1 (TfR1) mRNA level in placenta, as shown by cDNA microarray analysis and quantitative RT-PCR, by a mechanism which is independent of placenta iron content and iron responsive element/iron regulatory protein (IRE/IRP) activity. On the contrary, iron injections into pregnant mothers result in increased placenta iron and fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 29 publications
3
25
0
3
Order By: Relevance
“…40,41 The positive association between cord hepcidin and placental levels of soluble transferrin receptor was initially unexpected given earlier findings of an inverse association from the transgenic Thep27 mouse line, in which fetal hepcidin from constitutively hepcidin-expressing offspring was shown to downregulate placental transferrin receptor mRNA. 42 However, further investigation showed that high (i.e., above median) placental levels of soluble transferrin receptor were coincident with lowered maternal ferritin (P = 0.019, Wilcoxon rank-sum test) and normal cord ferritin (P = 0.48, Wilcoxon rank sum test), suggesting that the elevated placental soluble transferrin receptor could be, as previously described, a compensatory mechanism by which the placentas of iron-depleted mothers may enhance transfer of iron to the fetuses despite maternal iron deficiency, thereby mediating conflicting maternal-fetal iron demands. 43 Building on the hypothetical framework of the Atkinson and others' (2015) study that explored whether healthy child hepcidin concentrations could influence subsequent susceptibility to malaria, we investigated the prospective associations of cord hepcidin with risks of anemia, malaria, and mortality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…40,41 The positive association between cord hepcidin and placental levels of soluble transferrin receptor was initially unexpected given earlier findings of an inverse association from the transgenic Thep27 mouse line, in which fetal hepcidin from constitutively hepcidin-expressing offspring was shown to downregulate placental transferrin receptor mRNA. 42 However, further investigation showed that high (i.e., above median) placental levels of soluble transferrin receptor were coincident with lowered maternal ferritin (P = 0.019, Wilcoxon rank-sum test) and normal cord ferritin (P = 0.48, Wilcoxon rank sum test), suggesting that the elevated placental soluble transferrin receptor could be, as previously described, a compensatory mechanism by which the placentas of iron-depleted mothers may enhance transfer of iron to the fetuses despite maternal iron deficiency, thereby mediating conflicting maternal-fetal iron demands. 43 Building on the hypothetical framework of the Atkinson and others' (2015) study that explored whether healthy child hepcidin concentrations could influence subsequent susceptibility to malaria, we investigated the prospective associations of cord hepcidin with risks of anemia, malaria, and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Clinicians monitored children's health statuses during sick visits and at routine visits occurring on a biweekly basis during the first 12 months of life and a monthly basis for any follow-up beyond the first year. Children's hemoglobin was measured at sick visits and during routine visits at approximately 3,6,12,18,24,30,36,42, and 48 months of age. Parasitemia by P. falciparum was determined after counting 200 leukocytes on Giemsa-stained thick blood smear of a sample collected by heel or finger prick during child visits.…”
Section: Methodsmentioning
confidence: 99%
“…It should be noted in this context that the inflammation and degenerative changes are most severe in the lumbar region and is progressively less more rostrally. It is possible therefore that dysregulation of IPR1 activity and TfR1 mRNA expression in the lumbar region may be attributable to inflammationmediated upregulation of hepcidin (Oates and Ahmed, 2007;Wang et al, 2008), which has been shown to downregulate TfR1 mRNA independent of IRE/IRP binding activity (Martin et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…13 In addition, animal studies revealed that hepcidin and iron levels in the fetal liver may also regulate maternal-fetal iron transport. [14][15][16] We aimed to study maternal and fetal hepcidin and other iron parameters to improve our understanding of human placental iron transport. Therefore, we retrospectively assessed plasma concentrations of these indices in primigravidae, as a function of placental P. falciparum infection and maternal anemia, and in corresponding cord-blood samples.…”
Section: Introductionmentioning
confidence: 99%